The Use of Dictionary for Arabic Language Textbook to Improve The Students' Reading Skill l Istikhdam al-Mu’jam li Kitab Ta’lim al-Lugah al-‘Arabiyyah li Tanmiyyah Maharah al-Qira’ah lada al-Talabah - Robbani, Abdullah Syahid; Romadhoni, Mohammad Sholehudin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
Some of the problems in Arabic Learning are the weakness of students in preserving, remembering, understanding, and the difficulty of the vocabulary, sentences, and text in the textbook. The researcher aimed to prepare the dictionary with Arabic Language textbook to improve the students' reading skill by collecting the vocabularies in the textbook with the suitable pictures. Then, the vocabularies are arranged alphabetically with how it works in example of the sentence so that it is easier to be memorized, remembered and understood. Finall, it hopefully can eliminate the difficulty in understanding their textbook. The type of this research was Research and Development with quantitative and qualitative research methods. The research data were obtained from pretest, post-test, and questionaires with 31 fifth graders in elementary school. Meanwhile interviews were conducted with the Arabic language teacher. The results of this research indicated that the use of the auxiliary dictionary for Arabic Language textbook developed by the researcher was effective to improve the reading skills of students in the fifth grade of elementary school. The additional vocabulary that students get from the dictionary developed their reading skills. Moreover, the sentences in the dictionary clarify and give students an idea of the use of vocabulary in sentences and become one of the vocabulary teaching strategies. Thus, this research suggested that the teacher should concern to the problems of the students in reading skills. Finally, the use of auxiliary dictionary could solve those problems.